Dari Tradisi Ke Modernitas: Manajemen Pemasaran Di Pondok Pesantren - Fahrina Yustiasari Liriwati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic boarding schools, as traditional Islamic educational institutions, have an important role in forming the character, morals and faith of the younger generation in Indonesia. In facing the demands of increasingly modern times, marketing management has become an integral part of the sustainability and development of Islamic boarding schools. This article discusses the importance of marketing management in the context of Islamic boarding schools, as well as the changes and challenges faced in finding a balance between tradition and modernity. Islamic boarding school marketing management involves identifying the target audience, developing an image and brand, utilizing technology, and measuring and evaluating results. Islamic boarding schools must understand who their potential students are, build a positive image, utilize technology, and measure the effectiveness of marketing efforts. The main challenge is to maintain traditional values ​​while opening up to elements of modernity. This can be achieved with technology integration, a unified approach, and partnerships with the business world. Proper marketing management allows Islamic boarding schools to remain relevant in educating the younger generation who are religiously and morally strong while remaining competitive in an increasingly modern world.Thus, marketing management in Islamic boarding schools is key to maintaining and enhancing their role in society, helping them move from tradition to modernity with success.